Improving The Understanding of Way Huwi Community Towards Water Quality for Drinking Purpose Using Door to Door Method - Luhut Siringoringo; Sandi Maulana (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
The atmosphere of the COVID 19 pandemic changed the pattern of community service. In this case the Door to Door method is the best choice. The area of ​​training is Way Huwi Village because of high economic growth. The principle of this method is that the speakers come to people's houses with the aim of disseminating the results of their research. The case study conducted in order to identify groundwater well specifically for drinking purposes. This method will be better applied if previous research has been done. The results of the training show that the community can only distinguish water quality based on physicality alone. We need train the community so they can understand the principles of water for drinking purpose. The community response was very good with the many questions asked. This might be different if done in a room with many participants